Pembuatan Keramik Berpori Berbahan Baku Tricalcium Phospate Dengan Metode Protein Foaming-Starch Consolidation - Pratama, Teddy; Fadli, Ahmad; Helwani, Zuchra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Porous Tricalciumphosphate (TCP) is a synthetic material that can be used as bone implant. Porous TCP production can be conducted by Protein Foaming-Starch Consolidation method that using yolk as an agent to form pore. This research aims to study the influence of process variables i.e time of sintering (1-3 hours), time of burning (1-3 hours) and mixing rate (100-200 rpm) toward physical, chemical and mechanical properties of porous TCP using Response Surface Methodology (RSM) also characteristic porous TCP. Analyzed respons were porosity, density and compressive strength. Product characteristic of TCP resulted of porousity was 69.71-81.88%, density was 0.569-0.951g/cm3 and compressive strength was 1.05-1.85 MPa. Data processing using second order model obviously seen from significant curvature. Significance level between variables can be seen from pvalue < 0,05 and lack of fit > 0,05 which show that model was corresponding toward the result. R2 obtained were Y1 = 0.9383%, Y2 = 0.9384% , Y3 = 0.9674%. The most affecting factor significantly towards all the responses was time of sintering that followed by time of burning and mixing rate. Optimum condition was obtained at 3 hours time of sintering , 3 hours time of burning and mixing rate of 100 rpm with the optimum value of response for porosity by 70.56%, density by 0.92 gr/cm3 and compressive strength 1.66 MPa.Keywords : bone implant, protein foaming-starch consolidation, response surface methodology, tricalcium phosphate.